Golf club characteristics and vertical force distribution associated with pitch and lob shots of different carry distances - Jinhee K.; Minji S.; Myeounggon L.; Youkyung K.; Changhong Y. (International Journal of Sports Science & Coaching, 2017)
The purpose of this study was to investigate the club characteristics and vertical force distribution of pitch and lob shots of 20 and 30m in female golfers from the Korean Ladies Professional Golf Association (age: 21.3±1.7 years; height: 161.5±4.4 cm; body weight: 60.3±5.6 kg; career: 7.5±1.7 years). Ten infrared cameras and two force plates were used to record the swing of each golfer. The test golf swings included a pitch and lob shot to target distances of 20 and 30 m. The carry distance for the 20 and 30m shots was affected by club shaft angle, loft angle, projected ball angle, and club head speed. Pitch and lob shots were distinguished by ball position, club shaft angle, loft angle, vertical force distribution, projected ball angle, and club head speed. For the lob shot, the ball was positioned about 6 cm toward the left foot from the center of the heel marker, compared to the ball position in the pitch shot for the 20 and 30m shots. In addition, the loft angle was 10° wider and the vertical force of the right foot was 4% greater than for the pitch shot. The projection angle of the ball for the 30m lob shot was 57°, while that for the pitch shot was about 47°. Taken together, the withinplayer between-task design and the realistic well-practiced goal-directed experimental tasks provided an opportunity to determine how individual players modify their control strategies to regulate shot distance and ball trajectory when using the same club. These findings have practical implications for coaches and for golfers aiming to improve their short game ability. ABSTRACT FROM AUTHOR